The land of stories : a Grimm warning - Colfer, Chris, 1990- (Colfer, Chris, 1990- Land of Stories., 2014)
After thirteen-year-old Conner returns to the Land of Stories and reunites with his twin sister, Alex, who is training to become the next Fairy Godmother, war breaks out in the fairy-tale world.